Cutaneous Ossifying Amyloidoma. (19th October 2022) - Requena, Celia; Diago, Adrian; Traves, Victor; Llombart, Beatriz; Nagore, Eduardo; Sanmartin, Onofre
Abstract: Amyloidoma, otherwise known as tumoral amyloidosis, is a localized deposition of amyloid (AL-type or AA type) without systemic amyloidosis. It is the rarest form of tissue amyloid deposition, and up to 7% of amyloidomas develop systemic amyloidosis.Cutaneous AL-type amyloidoma is considered by many authors as an unusual variant of primary cutaneous marginal zone lymphoma. Although cutaneous amyloidoma can form calcifications, ossification is extremely unusual, with only 1 case previously published to date.We report the case of a 75-year-old woman with voluminous and strikingly ossifying AL-type amyloidoma in the left pretibial skin. Her medical history included excision of hepatic hydatidic cysts 25 years prior and diffuse large B-cell lymphoma of the left parotid gland 8 years prior treated with chemotherapy and radiotherapy with complete response. After the diagnosis of amyloidoma, an extension study with cervical, chest, abdominal, and pelvic TC was performed, with no additional lesions found. Serum and protein electrophoresis revealed elevations in kappa light chain and IgA immunoglobulin levels but did not reveal monoclonal bands. In situ hybridization for immunoglobulin light chains showed monotypic kappa expression in plasma cells infiltrating the amyloidoma.Extensive ossification in amyloidomas can make diagnosis difficult; therefore, we describe an interesting case of this histopathologically peculiar amyloidoma.